Concentración de medios o concentración de temas en el periodismo digital peruano. Un acercamiento cuantitativo al problema - Pastor, Lorena (2020)
The article presents the experience of the Performing Arts Workshop in Ancón II Model Penitentiary, from the point of view of the artists who facilitate the experience. What senses unfold? What are the creative routes and processes? The artistic experience is embodied as a process that transcends the scene, proposing the production and circulation of discourses and performances from the voice of its protagonists: the young men and women inmates at the prison. The body constitutes the central axis of subjective, discursive and performative production. The authors reflect on the performing arts as the production of experiences and relationships in the context of deprivation of liberty, understanding the processes as explorations and bonds in constant construction, as well as a research space that questions them regarding the meaning of their work and their role as artists.